Method of efficiency estimation of aviation communication system with radiochannel diagnosing - Игнатов, В. А.; Тарасов, O. A.; Пенда, Ж. Ж. (Proceedings of National Aviation University (archive), 1999)
Offered is an original method of comparative efficiency analysis of aviation communication systems with radiochannel diagnosing. In order to receive quantitative estimation of the tested systems an imitation model, constructed on the basis of modern telecommunication equipment, is used. In the capacity of the criterium for optimization of diagnosing algorithms offered is the authenticity of network information transfer